Comunitarismo, sociedade civil e a reforma da educação na era FHC (1995-2002)/Communitarianism, civil society and the education reforms in Brazil during the Fernando Henrique Cardoso government (1995-2002) - Sidney Reinaldo da Silva; Marcos Vinicius Pansardi (Universidade Estadual de Campinas, 2007)
Este artigo discute a relação entre as reformas da educação e a concepção de sociedde civil na era FHC, a partir de uma crítica ao comunitarismo. Apontamos que a concepção de formação humana pressuposta nas reformas do período em questão, voltada para a aprendizagem do trade off econômico e moral (ajudar os pobres como forma de compensar os benefícios recebidos pela sociedade, como o emprego, bolsas de estudos) coaduna-se com o neoliberalismo e com o reforço da histórica cisão "moral" da sociedade brasileira. This paper argues the relationship between education reforms and the civil society conception in Brazil during the Fernando Henrique Cardoso government (1995-2002). We analizes the communitarian people moral formation conception of such reforms showing how it harmonises with the neoliberal values like the exigence of the apprenticeship of the economic and moral trade-off: the market rationality. But such a trend does not help the brazilian people eliminate his historical moral cision grounded on deep economic inequalities conected with an "imoral" social subornination even for liberal values.